Spin-four N=7 $$ \mathcal{N}=7 $$ W-supergravity: S-fold and double copy construction - Sergio Ferrara; Dieter Lüst (Journal of High Energy Physics, 2018)
Abstract In the present investigation we consider the possibility of having new massive, higher spin W-supergravity theories, which do not exist as four-dimensional perturbative models. These theories are based on a double copy construction of two supersymmetric field theories, where at least one factor is given by a N=3 $$ \mathcal{N}=3 $$ field theory, which is a non-perturbative S-fold of N=4 $$ \mathcal{N}=4 $$ super Yang-Mills theory. In this way, we can obtain as S-folds a new N=7 $$ \mathcal{N}=7 $$ (corresponding to 28 supercharges) W-supergravity and its N=7 $$ \mathcal{N}=7 $$ W-superstring counterpart, which both do not exist as four-dimensional perturbative models with an (effective) Langrangian description. The resulting field resp. string theory does not contain any massless states, but instead a massive higher spin-four supermultiplet of the N=7 $$ \mathcal{N}=7 $$ supersymmetry algebra. Furthermore we also construct a four-dimensional heterotic S-fold with N=3 $$ \mathcal{N}=3 $$ supersymmetry. It again does not exist as perturbative heterotic string model and can be considered as the heterotic counterpart of the N=3 $$ \mathcal{N}=3 $$ superconformal field theories, which were previously constructed in the context of type I orientfold models.